Synthesis and crosslinking study of isomeric poly(thioether ether imide)s containing pendant nitrile and terminal phthalonitrile groups. Issue 48 (22nd November 2016) - Mushtaq, Nafeesa; Chen, Guofei; Sidra, Lala Rukh; Liu, Yang; Fang, Xingzhong
Abstract : Upon crosslinking, phthalonitrile-terminated polyimidePN-PI (a–d) films exhibited better solvent resistance, and greater thermal and mechanical properties thanPI (a–d) films. Abstract : Two novel series of highly organosoluble and curable polyimides containing pendant nitrile groupsPI (a–d) and phthalonitrile-terminated polyimidesPN-PI (a–d) were prepared by solution polycondensation of isomeric bis(chlorophthalimides)s and 2, 6-dichlorobenzonitrile with 4, 4′-thiobisbenzenethiol. The inherent viscosities of these copolymers were in the range of 0.37–0.59 dL g −1 in N -methyl-2-pyrrolidone (NMP) at 30 °C. The phthalonitrile and pendant nitrile groups in isomeric poly(thioether-ether-imide)s were thermally crosslinked without a catalyst through thermal curing up to 280–360 °C, which led to the transformation from thermoplastic polymers to thermosetting polymers. All PIs before and after crosslinking were characterised by gel permeation chromatography (GPC), differential scanning calorimetry (DSC) and Fourier transform infrared (FT-IR) spectroscopy.PN-PI (a–d) andPI (a–d) were found to be highly soluble in some solvents, such as chloroform, dimethylacetamide, m -cresol, dimethlyformamide and N -methyl-2-pyrrolidone, while the crosslinked polymers were insoluble in all tested solvents. The crosslinking results of pendant nitrile and terminal phthalonitrile groups are also compared. Both series of PIs showed high thermal stability based on 5% weight loss temperature ( T 5% ) in the range of 471–509 °C and increased up to 35 °C after thermal curing. Polyimides showed high glass transition temperatures ( T g s) ranging from 191–213 °C as determined by DSC, but no detectable T g was observed after thermal heating, indicating the crosslinked structure of PIs. The mechanical properties also enhanced after the crosslinking of the copolymers. The tensile modulus and strength of the cured PI films were in the range of 3.3–4.7 GPa and 68–122 MPa, respectively, which were up to 62% and 35% higher than the uncured films.